2011
DOI: 10.1378/chest.11-0324
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Pulmonary Embolism Among US Decedents With Sarcoidosis From 1988 to 2007

Abstract: Background: A recently published report from the United Kingdom suggested an association between sarcoidosis and pulmonary embolism (PE). We sought to examine whether this association was present among US decedents with sarcoidosis. Methods: We used data from the National Center for Health Statistics to investigate the association between sarcoidosis and PE among US decedents from 1988 to 2007. Results: From 1988 to 2007, there were 46,450,489 deaths in the United States and 23,679 decedents with sarcoidosis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 24 publications
7
64
0
1
Order By: Relevance
“…Indeed, the prevalence of OSA in sarcoidosis has been reported to be 17%, which is much higher than what might be expected in a healthy patient population [32]. Finally, while chronic thromboembolic disease should be considered as a potential cause of or contributor to PH, acute pulmonary embolism might also warrant exclusion in the context of new acute or subacute shortness of breaths and/or signs of increasing right-sided heart failure [33,34].…”
Section: Pathophysiology Of Ph In Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the prevalence of OSA in sarcoidosis has been reported to be 17%, which is much higher than what might be expected in a healthy patient population [32]. Finally, while chronic thromboembolic disease should be considered as a potential cause of or contributor to PH, acute pulmonary embolism might also warrant exclusion in the context of new acute or subacute shortness of breaths and/or signs of increasing right-sided heart failure [33,34].…”
Section: Pathophysiology Of Ph In Sarcoidosismentioning
confidence: 99%
“…In the largest non-transplant cohort of 479 sarcoidosis patients followed f7 yrs, the factors influencing the development of respiratory failure included both radiographic findings of fibrosis and a vital capacity ,2.5 L. A vital capacity of ,1.5 L was present in all patients who subsequently developed end-stage disease [58]. The ISHLT listing guidelines are primarily based on studies examining the United Network of Organ Sharing (UNOS) database as well as a much smaller study of 43 patients from a single transplant centre [33,36,59]. Univariate analysis from this latter study demonstrated that resting hypoxaemia, PH (mPAP o35 mmHg), cardiac index f2 L?min -1…”
Section: Overviewmentioning
confidence: 99%
“…1 Patients with sarcoidosis are at higher risk for pulmonary embolism, raising the concern that systemic inflammation may increase the risk of hypercoagulability in this population. 17 Medications such as β-blockers, calcium channel blockers, sotalol, dofetilide, and amiodarone can also be used in the course of treatment, though there are no comparative data to guide antiarrhythmic drug selection.…”
Section: Discussionmentioning
confidence: 99%
“…Swigris et al found that PE as the cause of death was significantly more frequent in sarcoidosis patients comparing to others (2.54% and 1.13% respectively) [50]. Vorselaars et al found PE in 6.2% of the patients with severe sarcoidosis requiring immunosuppressive therapy other than corticosteroids [51].…”
Section: In Patients Who Are Candidates To Randomizedmentioning
confidence: 92%